Effective methods of estimates of acoustic fields in the ocean generated by moving sources. Issue 1 (2nd January 2016) - Rabinovich, Vladimir; Hernández Juárez, Josué
Abstract : We consider underwater acoustic fields generated by non-uniformly moving modulated sources. We introduce a large parameter which characterizing simultaneously a slowness of variations of source amplitudes, and their horizontal velocities, and a large distances between sources and receivers with respect to the characteristic length of the acoustic wave. We present the asymptotic formulas for the acoustic fields as a sum of propagating modes. Applying the spectral parameter power series method (SPPS method), we obtain an analytic form of the dispersion equation and the propagating modes. We show that the SPPS method is an effective tool for the numerical implementation of the underwater acoustic fields generated by non uniformly moving sources.